Synthesis, in silico studies and cytotoxicity evaluation of novel 1,3,4-oxadiazole derivatives designed as potential mPGES-1 inhibitors - KÜÇÜKGÜZEL, İLKAY; BİNGÖL ÖZAKPINAR, ÖZLEM (MARMARA UNIV, 2020)
A series of new 1,3,4-oxadizole derivatives containing thioether group, has been synthesized to investigate their mPGES-1 inhibitory activities. The synthesized compounds were also evaluated for their anticancer and COX-1/2 inhibitory activities. All compounds were checked for their purity using TLC and HPLC analyses. The melting points, elemental analysis, FT-IR, H-1-/C-13-NMR and LR-MS data were utilized for structural characterization. The most potent derivative was 2-[5-{[2-methyl-5-(propan-2-yl)phenoxy]methyl}-1,3,4-oxadiazol-2-yl)sulphanyl]-1-(phenyl)ethan-1-one 3a, which showed inhibitory activity against mPGES-1 with an IC50 of 4.95 mu M. Docking studies with mPGES-1 and COX-1/2 enzymes revealed their affinity and potential binding mechanism for the tested compounds.
Keywords: 1,3,4-Oxadiazoles; thioethers; mPGES-1 inhibition; COX-1/2 inhibition; anticancer activity; molecular docking; ADME prediction; PROSTAGLANDIN-E SYNTHASE-1; 5-MEMBERED HETEROCYCLIC THIONES; BIOLOGICAL EVALUATION; MOLECULAR DOCKING; ESSENTIAL OIL; CARVACROL; COX-2; CYCLOOXYGENASE-2; IDENTIFICATION; BIOSYNTHESIS